The marine industrial competitiveness of blue economic regions in China. (December 2015) - Yan, Xiao; Yan, Liang; Yao, Xi-Long; Liao, Ming
Abstract: Enhancing competitiveness of China's marine industry has become an urgent theoretical and practical issue for the Chinese government. This study creates a new competitiveness evaluation index system for China's marine industry that measures comprehensive capacity, industrial output capacity, research capacity and environmental protection capacity. The study analyses marine industrial competitiveness during 2006–2012 and classifies China's 11 major coastal regions into three competitive tiers. It is found that competitiveness of China's marine industry originates from its research capacity, followed by comprehensive capacity, industrial output capacity and environmental protection capacity. The analysis and tier classification show that marine industrial competitiveness is strong in Guangdong, Shandong and Shanghai. Tianjin, Zhejiang, Fujian, Liaoning and Jiangsu are moderately competitive. Hebei, Guangxi and Hainan are weakly competitive. Moreover, results show that strongly competitive regions did little to assist marine industrial competitiveness of neighbouring regions. The study offers policy suggestions to enhance marine industrial competitiveness in China's blue economic regions on the basis of these findings. Highlights: Regional research capacity contributes the most to marine industrial competitiveness. Tertiary marine industries (marine services) boost competitiveness more than primary and secondary marine industries. Strongly competitive regions can assist the marine industrial competitiveness of neighbouring regions.